Effect of ensiling and silage additives on biogas production and microbial community dynamics during anaerobic digestion of switchgrass. (October 2017) - Zhao, Xiaoling; Liu, Jinhuan; Liu, Jingjing; Yang, Fuyu; Zhu, Wanbin; Yuan, Xufeng; Hu, Yuegao; Cui, Zongjun; Wang, Xiaofen
Highlights: Anaerobic digestion (AD) of silage switchgrass was studied for the first time. Ensiling with additives reduced DM loss rate and enhanced the methane yield in AD. L. brevis + cellulase improved ensiling effect, and got the highest methane in AD. Firmicutes and Bacteroides were the dominant bacteria in AD. Abstract: Silage processing has a crucial positive impact on the methane yield of anaerobic treated substrates. Changes in the characteristics of switchgrass after ensiling with different additives and their effects on methane production and microbial community changes during anaerobic digestion were investigated. After ensiling (CK), methane yield was increased by 33.59% relative to that of fresh switchgrass (FS). In comparison with the CK treatment, methane production was improved by 17.41%, 13.08% and 8.72% in response to ensiling with LBr + X, LBr and X, respectively. A modified Gompertz model predicted that the optimum treatment was LBr + X, with a potential cumulative methane yield of 178.31 mL/g total solids (TS) and a maximum biogas production rate of 44.39 mL/g TS·d. Firmicutes and Bacteroidetes were the predominant bacteria in FS and silage switchgrass; however, the switchgrass treated with LBr + X was rich in Synergistetes, which was crucial for methane production.